A new IDH-independent hypermethylation phenotype is associated with astrocyte-like cell state in glioblastoma - Ana Luisa Costa; Daria Doncevic; Yonghe Wu; Lin Yang; Ka Hou Man; Anna-Sophie Spreng; Hannah Winter; Michael Nai Chung Fletcher; Bernhard Radlwimmer; Carl Herrmann (Genome Biology)
Abstract Background DNA methylation plays a crucial role in cancer development and progression and has been linked to genetically and clinically distinct tumor classes, including IDH-mutated and IDH-wildtype adult-type diffuse gliomas. Here, we identify a CpG-island methylator phenotype (CIMP) that characterizes the receptor tyrosine kinase 2 (RTK2) subtype of IDH-wildtype glioblastoma. Results This RTK2-CIMP affects genomic locations and cell functions distinct from those of IDH mutation-associated IDH-CIMP and suppresses the expression of its target genes. The RTK2-CIMP-region chromatin is characterized by a combination of repressive and activating marks, including polycomb-associated H3K27me3 and enhancer-associated H3K4me1, consistent with DNA methylation-mediated silencing of genes with bivalent-state promoters in neural progenitor cells. Functionally, RTK2-CIMP affects neuronal lineage genes and is significantly associated with astrocyte-like glioblastoma, suggesting that RTK2-CIMP is an epigenetic signature of the astrocyte-like cell state. Furthermore, we demonstrate that RTK2-CIMP can be induced by genetic manipulation in glioblastoma cells. Conclusions Our results suggest that RTK2-CIMP is a key contributor to cell-state plasticity in glioblastoma.